Exploration of cholinesterase and tyrosinase inhibitory, antiprotozoal and antioxidant effects of Buxus sempervirens L. (boxwood) - Orhan, Ilkay Erdogan; Erdem, Sinem Aslan; Senol, Fatma Sezer; Kartal, Murat; Sener, Bilge (Elsevier Science Bv, 2012)
The petroleum ether, chloroform, ethyl acetate, and methanol extracts of the aerial parts of Buxus sempervirens growing naturally in Turkey were investigated against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) as well as tyrosinase (TYRO) enzymes for their inhibitory activity using ELISA microplate reader. Antiprotozoal activity of the extracts was tested against the parasites; Plasmodium falciparum (malaria) and Trypanosoma brucei rhodesiense (human African trypanosomiasis) at 0.81 and 4.85 mu g/mL concentrations. As antioxidant activity contributes to antimalarial activity, the extracts were also tested for their 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, iron-chelating capacity, and ferric-reducing antioxidant power (FRAP). Total phenol and flavonoid contents in the extracts were determined spectrophotometrically. The alkaloid fraction of the chloroform extract afforded two major alkaloids named (+)-buxabenzamidienine (1) and (+)-buxamidine (2). Our results showed that, except for the petroleum ether extract, the extracts displayed high antimalarial and anti-BChE effects as well as quite high iron-chelation capacity. Therefore, we suggest that the active extracts in the antimalarial tests might be showing their effects through the mechanism of BChE inhibition and additionally iron-chelation ability. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Alkaloid; Anticholinesterase; Antimalarial; Antioxidant; Boxwood; Buxus sempervirens